2017
DOI: 10.4194/1303-2712-v17_3_08
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of fish meal (FM ) and macroalgae (M A) substitution with fermented soybean meal and rice bran were tested on a commercial diet in juvenile abalone. Abalone (21600) individuals were distributed equally to four diet treatments. Four experimental diets were prepared: a Std diet, FM 50, FM50+M A50 and FM50+MA100. The standard diet (Std) consists of FM (140 g/kg), fermented soybean meal (250 g/kg), corn gluten meal (34 g/kg), shrimp meal (30 g/kg), wheat flour (200 g/kg), dextrin (50 g/kg) and M A (250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Biological indices (shell length and width and the soft body weight) were well reflected from growth performance of abalone in this study. Similarly, the increased biological measurements of abalone agreed with improved growth performance of abalone (Ansary et al, 2019a(Ansary et al, , 2019bBaek et al, 2019;Choi et al, 2018;Jang et al, 2018;Lee et al, 2017;Myung et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Biological indices (shell length and width and the soft body weight) were well reflected from growth performance of abalone in this study. Similarly, the increased biological measurements of abalone agreed with improved growth performance of abalone (Ansary et al, 2019a(Ansary et al, , 2019bBaek et al, 2019;Choi et al, 2018;Jang et al, 2018;Lee et al, 2017;Myung et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…showing the proximate composition of the soft body of abalone was heavily affected by dietary nutrient contents (Cho et al, 2008;Choi et al, 2018;Jang et al, 2018;Lee et al, 2017;Mai et al, 1995aMai et al, , 1995bMyung et al, 2016). The feasibility and suitability of tunic meal of SS as the alternative sources for FM and MA in the EPs were well proved in this study and their application will lead farmers to create higher benefit in considering feed cost and improved growth performance of abalone.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The most important advantages of using fruit by-products as abalone diet are to reduce the dependence of abalone on MA, which is expensive and limited in seasonal availability with low nutrition, and to eradicate cost of waste compilation, transportation and management programme. Similarly, some studies have been reported comparable growth performance of aquatic animals including abalone fed the diets substituting MA with food and plant by-products (tuna by-product, tunic meal of sea squirt, rice bran and white radish by-product) for fish meal and MA Jeon, Kim, Myung, & Cho, 2014;Lee et al, 2016;Lee, Kim, Choi, et al, 2017a;Lee et al, 2018). The desirable effect of citrus peel on growth of land animals, such as rats (Lim, Lee, & Kim, 2014), broiler (Ebrahimi, Qotbi, Seidavi, & Bagar, 2014;Siyal et al, 2016) and rabbit (Ojabo, Adenkola, & Odaudu, 2012), has also been reported.…”
Section: Discussionmentioning
confidence: 89%